The Antique Motifs in the “Livre d’Art” of the First Half of the 20th Century as the Example of the Problem of Tradition and Neomythologism in the Modern Art - Zinevich, Olga N. (Actual Problems of Theory and History of Art, 2013)
The article is aimed at analysing the following issues: specificity of the livre d’art of the first half of the 20th c. and its connection with the problems of the ancient, tradition, classic, quiescence, which were relevant for the period. In addition, the strong point of the article is the description of “mythological memory” and neo-mythologism in the works of the studied artists — Pablo Picasso, Henri Matisse, Henri Laurens, Aristide Maillol. In conclusion, the possible causes of the unique situation in the arts in this period are pointed out, as well as its comparison with the post-modern solutions.
Keywords: livre d’art; antique motives; tradition